KEBIJAKAN POLITIK PENDIDIKAN TINGGI PEMERINTAH KOLONIAL BELANDA DI INDONESIA (1920-1942) - Hendri Hendri (Diakronika, 2017)
The history of higher education in the Republic of Indonesia primarily on August 19, 1945, that was the founded of Balai Perguruan Tinggi Republik Indonesia (BPTRI) in Jakarta, upstairs of personage Indonesian higher education. However, if we look back as a long time, before freedom of Indonesian (August 17, 1945), actually the higher education in Indonesia had been founded, even had formed of system’s based on religions (Buddha, Islam, and Christian). Islamic people had founded institutes of Islamic education, for example Surau, Pesantren, Madrasah, etc, as well as with Christian that brought of colonialist (Dutch) to Indonesia. Dutch colonialist founding and make reorganizing to higher education them star at 1920-1942. They did it because certaint reasons, priority to fuulfil they need oftheir colonialism and they economic’s advantages from Indonesia. The higher education had they founded are THS te Bandoeng (1920), RHS te Batavia (1924),GHS te Batavia (1927), FLeW Batavia (1940), dan FvLw Buitenzorg (1941). At Republik Indonesia Serikat (1950’s), this higher education to be formed faculties of Universiteit Indonesia/BPTRIS.